2016
DOI: 10.1515/aoas-2016-0010
|View full text |Cite
|
Sign up to set email alerts
|

1. Insects – A Natural Nutrient Source for Poultry – A Review

Abstract: the consumption of poultry meat and eggs is expected to increase considerably in the nearest future, which creates the demand for new poultry feed ingredients in order to support sustainable intensive production. Moreover, the constant improvement of the genetic potential of poultry has resulted in an increased nutrient density in poultry feeds, which limits the possibility to include low quality feed ingredients. therefore, the feed industry needs new sources of highly digestible protein with a desirable amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
102
1
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(120 citation statements)
references
References 41 publications
4
102
1
13
Order By: Relevance
“…For adult females of the same species, Bosch et al (2014) reported high contents of valine, leucine, histidine, lysine and arginine, which is consistent with the levels found in B. dubia in this study. Moreover, Józefiak et al (2016) studied the EAA composition of B. lateralis subadult nymphs and found that tyrosine, arginine, valine and lysine were among the first five EAAs, which corresponds to the results obtained in this study. On the other hand, …”
Section: Discussionsupporting
confidence: 88%
“…For adult females of the same species, Bosch et al (2014) reported high contents of valine, leucine, histidine, lysine and arginine, which is consistent with the levels found in B. dubia in this study. Moreover, Józefiak et al (2016) studied the EAA composition of B. lateralis subadult nymphs and found that tyrosine, arginine, valine and lysine were among the first five EAAs, which corresponds to the results obtained in this study. On the other hand, …”
Section: Discussionsupporting
confidence: 88%
“…Performance results after 15 d showed no significant differences among treatments. Fresh MW larvae contained 40% DM and 1.0-4.5% total ash (Józefiak et al 2016). The above stated results are main causes for limiting their supplement (up to 10% of DM of total diet) in the broiler diets.…”
Section: Effect Of Mealworm On Poultry Performancementioning
confidence: 90%
“…The minimum and maximum values of CP, EE, ash, CF and energy in MW larvae were reported as 45-60% (Józefiak and Engberg 2015), 25-43% (van Broekhoven et al 2015;Józefiak and Engberg 2015), 3.0-4.5% (RamosElorduy et al 2002;Józefiak and Engberg 2015), 5.0-8.8% (Ramos-Elorduy et al 2002;Józefiak and Engberg 2015) and 244-781 cal/kg DM, respectively (Finke 2002;De Marco et al 2015). The total CP content of MW adult, exuvium and excreta were reported as 63.34, 32.87, and 18.51%, respectively (Ravzanaadii et al 2012).…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Reviews on the nutritive value of different insects and their meals including black soldier fly larvae, housefly maggot and pupae, mealworms, silkworm pupae, as well as locusts, grasshoppers and crickets demonstrate their potential application as an alternative protein source in the nutrition of different livestock species (Makkar et al, 2014;Sánchez-Muros et al, 2014;Józefiak et al, 2016). However, little is known about their possible secondary effects which can be related to a wide range of small peptides known as antimicrobial peptides (AMPs).…”
Section: Introductionmentioning
confidence: 99%